Coseismic Stress Change and Viscoelastic Relaxation after the 2008 Great Sichuan Earthquake - Chaodi Xie; Ye Zhu; Yingfeng Ji; Weiling Zhu; Rui Qu; Yan Xu; Aitang Li (Applied Sciences, 2022)
Long-term stress accumulation influenced by coseismic stress changes and postseismic viscoelastic relaxation is considered critical to triggering giant earthquakes. Nevertheless, how the stress increase is interrupted by aftershocks and how it influences the megaseismic cycle remain enigmatic. In this study, based on the Mohr–Coulomb failure criterion at the nucleated segments of the 2008 great Sichuan earthquake, the stress variation associated with four M > 6 aftershocks was calculated for the period from 2010 to 2017. The results show that (1) the spatial distribution of coseismic stress change is correlated with the rupture pattern of large events and has a fundamental impact on triggering subsequent earthquakes and (2) postseismic viscoelastic relaxation leads to increased Coulomb stress accumulation at the northern and southern edges of the seismogenic Longmenshan fault, which results in enhanced fault instability and the potential for future large events.